2014
DOI: 10.1589/jpts.26.1321
|View full text |Cite
|
Sign up to set email alerts
|

Change the Myofascial Pain and Range of Motion of the Temporomandibular Joint Following Kinesio Taping of Latent Myofascial Trigger Points in the Sternocleidomastoid Muscle

Abstract: [Purpose] The purpose of this study was to identify the changes in the myofascial pain and range of the motion of temporomandibular joint when Kinesio taping is applied to patients with latent myofascial trigger points of the sternocleidomastoid muscle. [Subjects and Methods] The subjects were 42 males and females aged 20 to 30 years (male 17, female 25). They were randomly divided into the control group and the experimental group, which would receive Kinesio taping. Kinesio taping was applied to the sternocle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 14 publications
1
25
0
1
Order By: Relevance
“…A similar result was found with the application of the EB in patients with latent TP in the sternocleidomastoid muscle, with a pain reduction and increase of the range of motion of the joint when compared to the group control, which did not receive care 1 .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…A similar result was found with the application of the EB in patients with latent TP in the sternocleidomastoid muscle, with a pain reduction and increase of the range of motion of the joint when compared to the group control, which did not receive care 1 .…”
Section: Discussionsupporting
confidence: 77%
“…The myofascial pain syndrome is a muscular condition caused by trigger points (TP), attributed to repetitive effort, maintenance of incorrect postures, musculoskeletal disorders, systemic diseases, sedentary lifestyle, and sleep disorders 1,2 . Teachers constitute an occupational group with a high prevalence of musculoskeletal pains.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kumbrink et al (17) used taping for the muscles and ligaments on the diseased side, which was combined with correction taping on the contralateral fascia in order to achieve relaxation of the important muscles affecting the mandibular movement and improvement of joint mechanics. Bae (31) used KT on the latent myofascial trigger points of the sternocleidomastoid muscle and observed that taping could significantly lower the Visual Analogue scale (VAS) score of the myofascial pain and improve the motion of TMJ. All these findings can be utilized for the improvement of the taping method.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, KT can produce continuous sensory input to the skin sensors, which may relatively suppress the sensory input of pain perception (32). An additional possible explanation for functional performance, disability or improvements in ADL is that application of KT may increase the range of motion of the temporomandibular joint during exercise (33).…”
Section: Discussionmentioning
confidence: 99%